Considering trilingual education - Henn-Reinke, Kathryn (New York : Routledge, 2012)
Based in case studies conducted in the US, Europe, and Latin America, this book explores the feasibility and benefits of trilingual/ multilingual education in the United States. Currently, there are few programs in the country of this nature, as educators tend to conclude that English-language learners would be overwhelmed by study in additional languages. Henn-Reinke builds an argument supporting trilingual education in the US, discussing issues of identity, curriculum, pedagogy, and the impact of other psycho-socio-linguistic factors
Includes bibliographical references and index.
Keywords: Multilingualism; Language and languages; Language acquisition